2020
DOI: 10.1080/09669582.2020.1818086
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of affective commitment between corporate social responsibility and eWOM in the hospitality industry

Abstract: Although previous research establishes customer reactions to companies' corporate social responsibility (CSR) actions, little is known about the effect of CSR on customers' affective commitment and their positive electronic word of mouth (eWOM). This study examines i) which perceptions of the three CSR activities (environment, society, and stakeholders) influence customers' affective commitment and positive eWOM, and ii) the mediating effects of affective commitment on the relationships between CSR activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 68 publications
0
14
0
5
Order By: Relevance
“…Affective commitment is also related to proactive work behavior (Luu, 2017) 2015). In the marketings' study, affective commitment is related to customer orientation (Lombardi et al, 2019) and electronic word of mouth (Mohammed & Al-Swidi, 2020). It confirms that affective commitment has an immense contribution to individuals and then has implications for the dynamics of organizational life.…”
Section: Affective Commitment and Ocbmentioning
confidence: 69%
“…Affective commitment is also related to proactive work behavior (Luu, 2017) 2015). In the marketings' study, affective commitment is related to customer orientation (Lombardi et al, 2019) and electronic word of mouth (Mohammed & Al-Swidi, 2020). It confirms that affective commitment has an immense contribution to individuals and then has implications for the dynamics of organizational life.…”
Section: Affective Commitment and Ocbmentioning
confidence: 69%
“…In particular, three items were adopted from [ 45 ] to assess IP-GCSR, eight items were adopted from [ 92 ] to assess GC, and 10 items were adopted from [ 25 ] to assess GATB (4), GSN (3), and GPBC (3) of the TPB. In addition, four items used to assess GPB were adopted from [ 16 ], five items used to assess WSE were adopted from [ 18 ], three items used to assess IVER were adopted from [ 21 ], three items used to assess WPPP were adopted from [ 20 ], and three items used to assess SCI were adopted from [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mohammed & Al-Swidi [ 45 ] define GHs as “Hotel [s] that perform eco-friendly policy or green management with social responsibility to protect environment but keeping the existing hotel value or service quality”. The purpose of GHs is to preserve cultural and natural resources by providing environmental responsibility to both customers and employees and making a contribution to the local community and activating it.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the restaurant industry, CSR communication with relevant stakeholders is important to enhance the shareholder value and improve the financial performance ( Kim and Kim, 2019 ). As some of the primary stakeholders, customers can support and engage in communication through CSR programs ( Pérez and del Bosque, 2015 ; Kim, 2017 ; Kim and Stepchenkova, 2020 , 2021 ; Raza et al, 2020 ; Girardin et al, 2021 ; Mohammed and Al-Swidi, 2021 ; Shafiee and Tabaeeian, 2021 ). Previous research demonstrated that consumers who have trustful relationships with the brand are more inclined to share their experience with others ( Bahri-Ammari et al, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%